Effect of organic loading rate (OLR) of slurry on biogas production quality - Mel, Maizirwan; Nadiah, Mohd Suhuli; -, Avicenna; Ihsan, Sany Izan; Ismail, Ahmad Faris; Yaacob, Sarifah (2014)

(untitled)
In this study, three different concentration of organic loading rate (OLR) were investigated to examine the effect of the change in the organic loading rate on the efficiency of the biogas production. Daily amount of biogas of different type of organic loading rate (OLR), rates of production of biogas, removal efficiencies of chemical oxygen demand (COD), total solid (TS) matter, volatile solids (VS) matter from the slurry were investigated in 30 days retention tyme using 50 L digester. The digester was operated at different organic feeding rates of 25000 mg/L COD, 50000 mg/L COD, and 75000 mg/L COD. The material used in this system is the fruits waste, vegetables waste and cow dung. The system operated in continuous system. The reactor showed stable performance with the highest quality of methane (concentration about70.3% of CH4) and rate of biogas production is 38.1 L/day with COD reduction of 52.1% during organic loading rate 50000 mg/L COD. As the organic loading rate was increased, the COD degradation and biogas yield decreased. Based on this result, the OLR of 50000 mg/L COD is suggested as design criteria for pilot biogas production.